Multidisciplinary Treatment Approach of a Patient with Amelogenesis Imperfecta Superimposed by Thumb Sucking Habit: A Case Report - Omar A. El Meligy; Raed R. Gholman (Journal of King Abdulaziz University: Medical Sciences, 2023)
A seven-year-old boy was presented with discontent of his teeth appearance, mild teeth sensitiveness, bad masticatory effectiveness, difficulty in speech and low self-esteem. The clinical and radiographic results indicated amelogenesis imperfecta. Because of uncooperative behavior, treatment was accomplished under general anesthesia. The use of composite resin and stainless steel crowns produced effective and satisfying improvement of the patient’s aesthetic looks, in addition to prevention of further sensitivity and wear so enhancing his functional needs. The lastingness of the thorough management of this patient needed powerful stress on careful oral hygiene. There is a major role of multidisciplinary team to the effective management of patients with hypomaturation type of amelogenesis imperfecta. Many factors have a significant part in treatment planning of amelogenesis imperfecta cases such as patient’s age, socioeconomic condition, seriousness of the defect, the patient’s collaboration and association with other medical conditions.